Incidence of active tuberculosis among people living with HIV receiving long‐term antiretroviral therapy in high TB/HIV burden settings in Thailand: implication for tuberculosis preventive therapy. Issue 4 (5th April 2022) - Suwanpimolkul, Gompol; Gatechompol, Sivaporn; Kawkitinarong, Kamon; Ueaphongsukkit, Thornthun; Sophonphan, Jiratchaya; Siriyakorn, Nirada; Jirajariyavej, Supunnee; Khusuwan, Suwimon; Panarat, Palakorn; Wannalerdsakun, Surat; Saetiew, Natcha; Chayangsu, Sunee; et al.
Abstract: Introduction: Among high tuberculosis (TB) and HIV burden countries in Asia, tuberculosis preventive therapy (TPT) in people living with HIV (PLWH) has been underutilized despite its proven benefits independent of antiretroviral therapy (ART). Therefore, we determined the incidence of active TB and mortality among 9179 adult PLWH who attended and received ART from 15 tertiary care hospitals across Thailand. Methods: A retrospective study was conducted in 2018 using follow‐up data from 1999 to 2018. The primary endpoint was incident TB disease after ART initiation. Factors associated with TB incidence were analysed using competing risk regression. The Kaplan–Meier method was used to estimate mortality after ART initiation. Results: During a median of 5.1 years of ART (IQR 2.2–9.5 years), 442 (4.8%) PLWH developed TB (TB/HIV), giving an overall incidence of 750 (95% CI 683–823) per 100, 000 persons‐year of follow up (PYFU). In multivariate analysis, lower CD4 at ART initiation (≤100 cells/mm 3, adjusted sub‐distribution hazard ratio [aSHR]: 2.08, 95% CI, 1.47–2.92; 101–200 cells/mm 3, aSHR: 2.21, 95% CI, 1.54–3.16; 201–350 cells/mm 3, aSHR: 1.59, 95% CI, 1.11–2.28 vs. >350 cells/mm 3 ), male sex (aSHR: 1.40, 95% CI, 1.11–1.78), lower body weight (<50 kg, aSHR: 1.52, 95% CI, 1.17–1.95) and prior TB event (aSHR: 3.50, 95% CI, 2.72–4.52) were associated with TB incidence. PLWH with HIV RNA ≥50 copies/ml had 5–9 times higher risk of active TB disease higher than those with HIV RNA <50 copies/ml at the same CD4 level. The risk for developing TB was remarkably high during the initial period of ART (175, 511 per 100, 000 PYFU at<3 months) and was comparable to the general population after 10 years of ART (151 per 100, 000 PYFU). TB/HIV had higher mortality (10% vs. 5%) and poorer HIV treatment outcomes: HIV RNA <50 copies/ml (63.8% vs. 82.8%), CD4 cells count (317 vs. 508 cells/mm 3 ) at the most recent visit. Conclusions: In this high TB burden country, TB incidence was remarkably high during the first few years after ART initiation and thereafter decreased significantly. Rapid ART initiation and appropriate TPT can be potential key interventions to tackle the TB epidemic and reduce mortality among PLWH in TB/HIV high burden settings.